Optimization of Tuned Mass Damper for Submerged Floating Tunnel with Frequency-Domain Dynamics Simulation - Jin, Chungkuk; Kim, Sung-Jae; Kim, MooHyun (Journal of Advances in Applied & Computational Mathematics, 2022)
In this study, the Tuned Mass Damper (TMD) optimization is carried out to reduce the resonant motion of Submerged Floating Tunnel (SFT) under wave excitations. The SFT dynamics is evaluated in frequency domain; a new approach to cost-effectively optimizing TMD parameters for a moored system is suggested. Discrete-Module-Beam (DMB) method is used to model the Tunnel; mooring lines are included as equivalent stiffness matrix through static-offset tests by the fully coupled model. Since the frequency-domain dynamics simulation model is employed, a significant reduction in optimization time can be achieved. TMD is installed at the tunnel’s mid-length to mitigate the lateral motion of the Tunnel and coupled with the Tunnel with translational and rotational springs and dampers. The optimization process for TMD parameters is performed through the Genetic Algorithm (GA). The GA generates the TMD mass and spring and damping coefficients. The dynamics simulation is performed under wave conditions and this process is repeated until the stopping criteria is satisfied. Results demonstrate that TMD with optimized parameters significantly reduces the lateral motion, especially near the system’s lowest lateral natural frequency. This frequency-domain optimization also works as intended with significantly decreased optimization time.